Geology of northwest Panay A peek into the leading edge of a continental terrane - Montes, Mary Grace S. Asio
The Palawan microcontinental block is a major terrane that influenced the Cenozonic evolution of the Philippine archipelago.Its Early Miocene docking onto the Philippine mobile belt juxtaposed continent-derived rocks of the Buruanga Peninsula are observed adjacent to the rocks of the Antique Range of oceanic and island arc affinity. In view of understanding better this arc-continent collision, field geologic investigation is carried out in northwest Panay. Northwest Panay offers an ideal setting as very limited investigations have been done in the area to decipher the collision event in this part of the region. Consequently, new lithostratigraphic units are recognized thereby redefining its geology and stratigraphy.An alternating sequence of chert and clastic rocks juxtaposed with limestone bodies serves as basement of the Buruanga Peninsula. Herein introduced as the Unidos Formation, Saboncongon Formation and Gibon Formation, respectively, they represent the remnant stratigraphy of an oceanic plate preserved in an accretionary wedge. Based on the radiolarian assemblage in the chert and siliceous mudstone from the Unidos and Saboncogon Formation, respectively, the time of formation and pre-Cenozoic tectonics of the Buruanga Peninsula is constrained. Correlation with the chert-clastics-limestone sequence in the Calamian Islands in Palawan likewise, shows similarity in age and lithology between the two regions. Following the tectonic model of Zamoras (2001) for the Calamian Islands, it is modelled that this section (i.e., chert-clastics-limestone sequence) of northwest Panay is part of NW-traveling Mesozoic oceanic plate (i.e., Izanagi Plate) that subducted at the southern portion of East Asian subduction zone. Consequently, this provides linkage with the other accretionary complexes in the East Asian margin and SW-NE Japan.Similarly, lithostratigraphic and chronostratigraphic resemblance of the Unidos, Saboncongon and Gibon Formations with the chert-clastics-limestone sequences in Palawan proves the continental origin of the Buruanga Peninsula, i.e. former part of mainland Asia. Petrographic investigation of the sandstones from the Saboncongon Formation further strengthens this contention. With the abundance of quartz, a continental source area is inferred.Other lithostratigaphic units observed in the peninsula are the Patria Quartz Diorite, Buruanga Metamorphics and the Libertad Formation. The Early Miocene Patria Quartz Diorite intrudes the Gibon Formation thereby marbleizing the limestone in its contacts aureole. The Buruanga Metamorphics, however, is thought to be the metamorphosed variety of the Saboncogon Formation based on petrographic and field evidences (e.g., high amount of quartz content and field relationship). The Libertad Formation is a Plio-Pleistocene succession of marl, sandstone, mudstone, conglomerate and limestone which caps the stratigraphy of the Buruanga Peninsula. This formation is likewise observed in the Antique Range.The Antique Range lies east of the Buruanga Penisula. Found within the terrane is the ultramafic component of the Antique Ophiolite Complex, the Middle Miocene Fragante Formation and the late Middle Miocene Lagdo Formation. Sandstone petrography from the Fragante and Lagdo Foramtions reveals low amount of quartz fragments and high amount of lithic, feldspar and matrix content implying an island arc origin.With the marked difference in age and lithology between the Buruanga Peninsula and Antique Range, there should exist a tectonic boundary. The Buruanga Peninsula is inferred to be continental in origin whereas, the Antique Range contains tectonic slivers of oceanic, island arc and continent derivation. The Buruanga Peninsula is made up of Jurassic chert-clastics-limestone sequence the Antique Range is composed of an ophiolite basement unconformably overlain by Middle Miocene volcano-sedimentary units. These sedimentary units have oceanic-, continental- and arc-derived clasts. Since it is also argued that the accretion of the Antique Ophiolite Complex is a consequence of the PCM-PMB collision, it is interpreted that the collision zone lies within the Antique Range. The eastern extent of the collision zone may correspond to the eastern boundary of the Antique Range since it is shown that terranes (i.e., Iloilo Basin and Eastern Volcanic Arc) farther east of the Antique Range have a PMB affinity and thus are arc-related.